Clare Island Digital Health Project - using technology to enable health for all - Aoife Murray; Noreen Lineen-Curtis; Hemendra Worlikar; Derek O'Keeffe (James Cook University, 2023)
Introduction: Island communities have a different experience of health services compared with urban dwellers. Islanders face challenges of accessing equitable health services with varied availability of local services and the added difficulty of sea and weather conditions on top of the physical distance to reach specialised services. In a 2017 review of primary care island services in Ireland, it was proposed that telemedicine solutions could potentially improve delivery of health services. However, these solutions must meet the unique needs of the island population.Aims and Methods: This collaborative project brings together healthcare professionals, academic researchers, technology partners, business partners and the Clare Island community, to improve the health of the island population via novel technological interventions. The Clare Island project aims to identify specific healthcare needs of the island through community engagement, develop innovative solutions, and assess the impact of the interventions via a mixed-methods approach.Results: Preliminary engagement with the Clare Island community via facilitated round table discussions has identified Islanders’ overarching enthusiasm for digital solutions and added benefit of provision of 'health at home' for Island communities, particularly, the potential to better support the older person at home via technology. Key challenges including basic infrastructure, useability and sustainability of digital health initiatives were common themes identified. We also will discuss in detail the needs-led process of innovation of telemedicine solutions deployed on Clare Island. Finally, we will present the anticipated impact of the project and the challenges and opportunities of telehealth for island health services.Discussion: Technology has the potential to narrow the gap of inequity of health services for island communities. This project is an example of how through cross-disciplinary collaboration, and needs-led, specifically 'island-led', innovation of digital health solutions, the unique challenges for island communities can be addressed.